Bevz N. V. Hermeneutical-communicative aspects of untranslatability in the field of the translator’s culture - Bevz N. V. (Philological Treatises, 2020)
The article deals with some aspects of impossibility of translation, particularly on the basis of the analysis of «problem spaces» of philosophical texts. Untranslatability in philosophical texts is depicted in the lacuna of «silence», which represents the way of invitation to the dialogue, translator’s communication. In the whole, the solution of the problem of untranslatability can be the indicator of the quality of the translation in the translator’s culture.